In situ growth of g-C3N4 on TiO2 nanotube arrays: construction of heterostructures for improved photocatalysis properties - Lan, Ching Sim; Kai, Sheng Koh; Kah, Hon Leong; Yik, Heng Chin; Azrina, Abd Aziz; Saravanan, Pichiah (Elsevier Ltd, 2020)
n this work, we successfully constructed g-C3N4/TNTs heterostructures via in situ growth of g-C3N4on thesurface of TiO2nanotube arrays (TNTs). Varying concentrations of urea precursor were adopted to prepare thebinary composites for the photodegradation of methylene blue (MB). Advanced microscopic and spectroscopicapproaches such as FESEM, PL-Raman, UV–vis DRS, XRD and etc examined the topography, structural andoptical properties attributed to the presence of g-C3N4in the heterostructures. The morphological analysisshowed that the in-situ growth of g-C3N4onto the surface of TNTs significantly increased the wall thickness ofthe nanotubes. The least band energy of 1.8 eV was obtained by g-C3N4/TNTs (1.5 g) due to the formation of animpurity energy level induced by the presence of g-C3N4. The electron transfer between the heterojunction of g-C3N4and TNTs was revealed by the quenching of PL emission intensity. When the urea content was optimized at1.0 g, the build-in electricfield at the interface of g-C3N4/TNTs stimulated the electrons transfer and prolongedlifetime of carriers, thus enhancing the degradation efficiency by 1.25 times higher than that of pure TNTs.However, the aggregation of g-C3N4as a result of increasing urea content (1.5–2.0 g) reduced the interfacialadhesion at the heterojunction between the g-C3N4and TNTs, thus dominating its excellent optical and chargeseparation properties and diminishing the degradation efficiency of MB.